Histological Estimation of Ovaries Cystic Lesions in Iraqi Patients’ Women - Nori, Mustafa Sabah; Qasim, Ban J; Hussein, Alaa G (Iraqi Journal of Science, 2023)
Ovarian cystic lesions are one of the most common pathologic disorders in gynecology and a common reason for surgery. The purpose of the study was to determine the histopathologic characteristics of benign cystic ovarian lesions and their correlation to age, type, laterality, locularity, and size of ovarian cystic lesions. This is a retrospective study carried out on 100 cases from the archive in the Imam Kadhimian medical city and the educational laboratories of Baghdad medical city, out of 100 patients, the most common age group that underwent cystectomy was 20-40 years old. The vast majority of the cysts were non-neoplastic (67%) while the neoplastic cysts occupy 33% of all cysts. The most common non-neoplastic cyst was corpus luteum cyst (49 (49%) out of 100), subsequently follicular cyst (11 cases (11%) out of 100) and they are most commonly encountered in the age group (20 to 40) years while the most common neoplastic cyst was matured cystic teratoma (17 cyst (17%) out of 100) in the age group (20 to 40) years subsequently serous cystadenoma (12 cysts (12%) out of 100) in the age group (41-60) years. Most of the non-neoplastic cyst (58 out of 67) was measured less than 6 cm while most of the neoplastic cyst (22 out of 33) measured more than 6 cm and both appear slightly more frequent in the age group (20-40) years.